ChemInform Abstract: A FRET—ICT Dual‐Quenching Fluorescent Probe with Large Off—On Response for H2S: Synthesis, Spectra and Bioimaging. Issue 35 (September 2015) - Zhang, Changyu; Wei, Lv; Wei, Chao; Zhang, Jie; Wang, Runyu; Xi, Zhen; Yi, Long
Abstract Compound (I) is a sensitive and selective fluorescent probe for H2S in a buffer and in living cells.